C–H Bond Silylation of Heteroarenes - Khatua, Hillol; Das, Subrata; Patra, Sima; Chattopadhyay, Buddhadeb (Synthesis, 2023)
Organosilicon compounds are highly important molecular scaffolds with versatile synthetic utility, and are used in a range of transformations. Such organosilicon compounds are employed in a wide range of research areas, including medicinal chemistry, drug discovery, pharmaceuticals, agrochemicals, fine chemicals, etc. Moreover, they are commonly encountered in a number of commercial products. However, the preparation of organosilicon compounds by means of traditional methods significantly limit their wider applications. Recently, several new concepts and powerful methods have been developed in order to prepare organosilicon compounds via transition-metal catalysis or without metal catalysis. While many procedures have been reported for the silylation of aromatic systems, methods for the silylation of heteroarenes are scarce. Nevertheless several excellent and robust strategies for heteroarene silylation have been discovered. In this short review, we summarize the different methods, mechanisms and catalyst development for the regioselective silylation of heteroarenes.1 Introduction2 Silylation of C–H Bonds through Organometallic Intermediates2.1 Intermolecular C–H Bond Silylation Assisted by Directing Groups2.2 Undirected Intermolecular C–H Bond Silylation2.3 Intramolecular C–H Bond Silylation via a Tethered Silyl Unit3 C–H Bond Silylation with Silicon Electrophiles4 C–H Bond Silylation with Silicon Nucleophiles5 C–H Bond Silylation with Silyl Radicals6 Other Approaches6.1 Alkali-Metal-Catalyzed C–H Bond Silylation6.2 Magnesium-Promoted Reductive C–H Bond Silylation7 Conclusions and Outlook
Keywords: heteroarenes; silylation; functionalization; regioselectivity; C–H bond activation; silicon electrophile; silicon nucleophile; silyl radical